Ultrasound sorting increases feedlot profitability - Garmyn, A.; Moser, Daniel W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Feedlot managers often market entire pens as mixed groups, resulting in lower-quality, over-finished, or heavyweight carcasses. As the cattle industry has moved towards valuebased marketing systems, finding a costeffective tool that predicts future carcass merit and sorts cattle into outcome groups, thus producing a more uniform product at harvest, is of great interest to feedyard managers. The objective of this research was to determine the profitability of sorting feedlot cattle at reimplant time by using ultrasound and computer technology to group cattle into uniform market groups.
Keywords: Beef; Cattle; Ultrasound; Feedlot